Complex percutaneous biliary procedures: Review and contributions of a high volume team - Eduardo Houghton (Society of Gastrointestinal Intervention, 2019)
A comprehensive literature review was performed to evaluate the state of art and level of evidence of complex percutaneous biliary procedures and their safeness and effectiveness. Amidst those procedures, the review focused on techniques to achieve non-dilated biliary drainage, multiple self-expandable metallic stents, multiple plastic stents for the treatment of benign biliary strictures, simultaneous biliary and duodenal stent placement, rendezvous maneuvers, and use of magnets to treat biliary stenosis or even create new anastomosis with the jejunum or duodenum. A description of each technique and revision of literature provides useful tools for clinical practice decisions.